THE ROLE OF THE EDUCATOR IN IMPROVING THE LEARNING PROCESS THROUGH THE PAULO FREIRE PROBLEM METHOD - Aulia Nurjannah, Latifah Meynawati, R. Deti Rostika (Universitas Pakuan, 2022)
This research aims to look at how to improve the role of educators in the learning process, especially through Paulo Freire's problematic education concept. As it can achieve the expected goals in the learning process, the role of educators is very important. This study employs a qualitative method with a descriptive design in which it provides a careful description of certain individuals or groups about the conditions and symptoms that occur. In this study, the author uses data techniques based on analyzing the thoughts, biographies, and especially in the concept of problems with the perspective of Paulo Freire descriptively. Traditional methods are still widely used by educators today who are lacking in the learning process, which according to Paulo Freire is called the concept of bank style or the existence of oppression of students, with educators as the dominating party, and arguably are the same direction as students. In this case, the author uses the concept of Education Against Problems to streamline the learning process that can be used to achieve a goal. The educator along with the learner is placed as an educational subject who knows himself, in order to achieve more knowledge in the form of purity and knowledge as an object. Therefore both parties are in the same position as learners, and interact in providing knowledge information in a straight line.